1994
DOI: 10.1063/1.355531
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and crystallographic properties of Co-Cr-(Ta,Pt)/Cr films deposited by excimer laser ablation

Abstract: The crystal structure and magnetic properties of Co-alloy films deposited by KrF excimer laser ablation were investigated. A pulsed laser beam with wavelength of 248 nm was focused onto the deposition targets which were fixed in the vacuum chamber. Cr underlayer and Co-alloy films were successively deposited at a rate of 0.012 nmipulse. The film surface was microscopically smooth compared to the sputtered films. This may be due to the low-shadowing effect during the laser deposition. The composition of the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…PLD is therefore well suited to investigating the effects of arrival rate, kinetic energy, and ion bombardment on microstructural development in thin films. Previously, Ishikawa et al 5,6 reported that the Cr ͕100͖/CoCrPt ͕112 0͖ orientation formed at 450°C in bilayer films deposited by PLD, but at lower temperatures they found a fcc-Co phase with low coercivity. It is interesting to explore the PLD process further in the Cr/CoCrPt system, including in particular the effects of ion bombardment.…”
Section: Introductionmentioning
confidence: 98%
“…PLD is therefore well suited to investigating the effects of arrival rate, kinetic energy, and ion bombardment on microstructural development in thin films. Previously, Ishikawa et al 5,6 reported that the Cr ͕100͖/CoCrPt ͕112 0͖ orientation formed at 450°C in bilayer films deposited by PLD, but at lower temperatures they found a fcc-Co phase with low coercivity. It is interesting to explore the PLD process further in the Cr/CoCrPt system, including in particular the effects of ion bombardment.…”
Section: Introductionmentioning
confidence: 98%
“…In our experiment, the laser energy and deposition rate were as low as 1-3 J/cm 2 and 3 nm/1000 pulses, the CoCr films had HCP-Co structure with a few minor FCC-Co phases in some samples. Therefore, the magnetic properties have greatly improved in our films compared to that fabricated by Ishikawa [9].…”
Section: Article In Pressmentioning
confidence: 83%
“…Ishikawa et al [9] had deposited CoCrM(30 nm)/ Cr(50 nm) at 250 1C by PLD. The maximum deposition rate of the Co-alloy film was 12 nm/1000 pulses (four times greater than ours) with energy density of the laser beam of 10 J/cm 2 .…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft magnetic films are used in writing heads for magnetic data storage, audio and video applications, and have prospective applications in magnetic sensors, switches, and concentrators. Complex CoCr(Ta,Pt) alloys [Ishikawa et al, 1994] prepared by PLD combine coercivities (m 0 H c ) of 0.013-0.025 Tesla with a film smoothness improved over that of sputtered samples. Amorphous magnetic FeCoNiSiB films have been produced by laser ablation from amorphous magnetic ribbons [Nikitin et al, 1997].…”
Section: Soft and Hard Magnetic Materialsmentioning
confidence: 99%